GERMAN HOUSING POLICY AND THE CURRENT STATE OF THE HOUSING MARKET IN GERMANY - Richter, Julia (Sociedade e Território, 2023)
Since it began with the founding of the Federal Republic of Germany in 1949, politicians have tried to alleviate crises with a social housing policy and to use various instruments to ensure that the population can adequately meet their housing needs and reduce socio-economic and regional disparities. Some of these instruments are aimed at creating affordable living space (social housing) or controlling rental prices (rent brake). Others serve to promote home ownership (housing allowance) and thus serve more for middle-income groups .